THE PREVALENCE AND CLINICAL SIGNIFICANCE OF PERINUCLEAR ANTINEUTROPHIL CYTOPLASMIC ANTIBODY IN PATIENTS WITH INDETERMINATE COLITIS - Mahdi, Batool Mutar; Hasan, Riyadh Mohamad; Maki, Bassma; Hazim, Wafaa; Ghanim, Nahla; Al-Galabi, Leen Khalog (AL-Kindy College Medical Journal, 2011)
Background: Indeterminate colitis (IC), a term originated by pathologists to characterize confounding histopathlogic appearance of resected mucosa, has become catch phrase for cases in which diagnostic criteria at all levels elude classification as Crohn’s disease (CD) or ulcerative colitis (UC). OBJECTIVES: evaluate the prevalence of pANCA expression in the sera and its isotypes. Patients and methods: PATIENTS GROUP consisted of 60 patients (40 males and 20 females) with indeterminate colitis and their age range was (19- 84 years). CONTROL GROUP consisted of 30 (15 males and 15 females) healthy volunteers and their age range was (20- 66 years). Antineutrophil cytoplasmic ( pANCA and cANCA) testing was performed by an IIF technique on ethanol fixed human EOH granulocytes as substrate (EUROIMMUNE- Germany). Sigmoidoscope and colonoscope examination were done for the patients group and biopsies were taken from the patients for histopathological examination. Results: Serological results of ANCA showed a significant increased frequency of pANCA (63.3%) in indeterminate colitis patients as compared to controls (p=0.000). The highest percentage of this pANCA titer was 1:10 (p=0.000) then 1:100 (p=0.008) and most of them was IgG (53.3%) (p=0.000). Sensitivity of pANCA was 60%, specificity of pANCA was 40%, positive predictive value of pANCA was 61.1% and negative predictive value of pANCA was 66.6%. cANCA did not demonstrated in both groups. Conclusions : pANCA was more prevalent in indeterminate colitis and could be used as a predictive serological marker for the outcome of disease.